Information Retrieval 8th Russian Summer School, RuSSIR 2014, Nizhniy Novgorod, Russia, August 18-22, 2014, Revised Selected Papers - Braslavski, Pavel; Karpov, Nikolay; Worring, Marcel; Volkovich, Yana; Ignatov, Dmitry I. (Communications in Computer and Information Science,, 2015)
This book constitutes the thoroughly refereed proceedings of the 8th Russian Summer School on Information Retrieval, RuSSIR 2014, held in Nizhniy Novgorod, Russia, in August 2014. The volume includes 6 tutorial papers, summarizing lectures given at the event, and 8 revised papers from the school participants.The papers focus on various aspects of information retrieval. .